2019
DOI: 10.1262/jrd.2019-022
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of developmental competence and <i>in vitro</i> growth culture of bovine oocytes

Abstract: Recently, the demand of transferable embryos in cattle industry is increasing, and the number of embryos produced in vitro is also increasing in the world. Although oocytes are collected from individual elite cattle by ovum-pick up (OPU) and used for in vitro production (IVP) of embryos, the cattle are mono-ovulatory animal. It means that most of oocytes collected from ovaries are destined to degenerate. To improve the IVP efficiency, we should predict the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…Taken together, and as stated by the review of Nagano and colleagues [69], a dark ooplasm indicates an accumulation of lipids and good developmental potential, light-colored ooplasm indicates a deficiency of lipid stores and poor developmental potential, and black ooplasm indicates aging and low developmental potential ( Figure 2). Finally, the use of NIC and CARS should be further investigated as a potential non-invasive tool to evaluate the lipid content of single oocytes in livestock species.…”
Section: Lipid Contentmentioning
confidence: 53%
See 1 more Smart Citation
“…Taken together, and as stated by the review of Nagano and colleagues [69], a dark ooplasm indicates an accumulation of lipids and good developmental potential, light-colored ooplasm indicates a deficiency of lipid stores and poor developmental potential, and black ooplasm indicates aging and low developmental potential ( Figure 2). Finally, the use of NIC and CARS should be further investigated as a potential non-invasive tool to evaluate the lipid content of single oocytes in livestock species.…”
Section: Lipid Contentmentioning
confidence: 53%
“…Moreover, brown oocytes with dark edge or with dark spots showed under electron microscopy an organelle arrangement similar to in vivo matured oocytes, and pale or black oocytes appeared to be degenerating and/or aging [67]. The authors concluded that a dark ooplasm is associated with a lipid accumulation and better developmental competence, while a pale ooplasm would indicate fewer amount of organelles and poor developmental potential [69]. Interestingly, a study by Prates et al [70] distinguished fat areas of different color shades using the Nomarski interference differential contrast (NIC) as the fat gray value of porcine oocytes, reflecting alterations in lipid content, and proposing this tool as an appropriate and non-invasive technique to evaluate the lipid content of a single oocyte before or after in vitro maturation.…”
Section: Lipid Contentmentioning
confidence: 97%
“…Taken together, and as stated by the review of Nagano and colleagues [66], a dark ooplasm indicates an accumulation of lipids and good developmental potential, light-colored ooplasm indicates a low density of organelles and poor developmental potential, and black ooplasm indicates aging and low developmental potential. Finally, the use of NIC should be further investigated as a potential non-invasive tool to evaluate the lipid content of single oocytes in other livestock species.…”
Section: Lipid Contentmentioning
confidence: 54%
“…In bovine reproductive biotechnologies, the oocytes from the large potentially dominant follicles (LFs, >8 mm) are more competent for in vitro embryo development than the oocytes from the smaller ones (<6 mm) [ 23 , 24 ], although the oocytes themselves have similar size. However, accumulation of lipids in the oocytes correlates with their competence to in vitro embryo development [ 25 , 26 ]. In cows, lipid composition of COC environment affected oocyte quality, in vitro and in vivo [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%